Has anyone seen Charlotte Salter? : a novel [large type] - French, Nicci (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
"On the day of Alec Salter's fiftieth birthday party, his wife, Charlotte, vanishes. Most of the small English village of Glensted is at the party for hours before anyone realizes she is missing. While Alec brushes off her disappearance, their four children-especially fifteen-year-old Etty-grow increasingly anxious as the cold winter hours become days and she doesn't return. Then Etty and her friend Morgan find the body of Morgan's father-and the Salters' neighbor- Duncan Ackerley, floating in the river. The police conclude that Duncan and Charlotte were having an affair before he killed her and committed suicide. Thirty years later, Morgan Ackerley returns to Glensted with his older brother to make a podcast based on their shared tragedy with the Salters. Alec, stricken with dementia, is entering an elder care facility while Etty helps put his affairs in order. But when the Ackerleys ask to interview the Salters, the entire town gets caught up in the unresolved cases. Allegations fly, secrets come to light, and a suspicious fire leads to a murder. With the podcast making national news, London sends Detective Inspector Maud O'Connor to Glensted to take over the investigation. She will stop at nothing to uncover the truth as a new and terrifying picture of what really happened to Charlotte Salter and Duncan Ackerley emerges"--